1
$\begingroup$

$a_n=a_{n-1}-6\cdot3^{n-1}$ for $n>0, a_0=0$

So I calculate first terms

$a_0=0$

$a_1=-6$

$a_2=-24$

$a_3=-78$

I don't see any relation so

$a_n=a_{n-1}-6\cdot3^{n-1}$

$a_{n-1}=a_{n-2}-6\cdot 3^{n-2}$

. . .

$a_2=a_1-6\cdot3^{1}$

$a_1=a_0-6\cdot 3^{0}$

Not sure what to do next, Wolfram solves it in this way:

$a_n=-3\cdot(3^{n}-1)$

How do I get to this point?

$\endgroup$
  • $\begingroup$ Welcome to TeX SX! Do you mean $a_n$ or $an$? $\endgroup$ – Bernard Jan 27 '19 at 13:07
  • $\begingroup$ Hello, yes I meant first option, didn't know how to do it in tex, sorry. $\endgroup$ – Gorosso Jan 27 '19 at 13:14
  • $\begingroup$ it's just a_{n}, a_{n-1}, &c. If there's only 1 character in subscript, the braces are not necessary. $\endgroup$ – Bernard Jan 27 '19 at 13:21
2
$\begingroup$

You have $$a_n=a_n=a_{n-1}-6\cdot 3^{n-1}=a_{n-2}-6\cdot 3^{n-2}-6\cdot 3^{n-1}=\dotsm,$$ so you can prove with an easy induction that $$a_n = a_0-6\sum_{k=0}^{n-1} 3^k=-6\frac{3^n-1}{3-1}.$$

$\endgroup$
2
$\begingroup$

hint...consider $$\sum_{r=0}^{r=n}(a_{r+1}-a_r)=\sum_{r=0}^{r=n}-6\cdot3^r$$

The LHS is a telescoping series and the RHS is a geometric series.

$\endgroup$
1
$\begingroup$

This is just a Geometric Series:

$$a_n=-6\sum_{i=1}^n3^{i-1}=-6\sum_{i=0}^{n-1}3^i=-6\times \frac {3^n-1}{3-1}=-3\times (3^n-1)$$

$\endgroup$
1
$\begingroup$

Note that for all $n$ we have $$a_{n+1}-a_n = -6\cdot 3^n $$

so we have also: $$a_n-a_{n-1}=-6\cdot3^{n-1}$$

thus $$a_{n+1}-a_n = 3(-6\cdot3^{n-1}) = 3(a_n-a_{n-1})$$

{or divide this two equations: $${a_{n+1}-a_n \over a_n-a_{n-1}}= {-6\cdot 3^n\over -6\cdot3^{n-1}} = 3$$}

so you have to solve linear recurrence:

$$ a_{n+1}-4a_n+3a_{n-1}=0$$

CAn you do that?

$\endgroup$
  • $\begingroup$ ok so: $x^{2}-4x+3$ $\Delta =4$ $x1=1$ $x2=3$ Now I use following formula $a_n=ar^{n}+br^{n}$ $a_0=0=a+b$ $a_1=-6=a+3b$ $a=-b$ $-6=2b$ $b=-3$ $a=3$ $a_n=3*1^{n}-3*3^{n}$ $\endgroup$ – Gorosso Jan 27 '19 at 14:40
  • 1
    $\begingroup$ Yes, that is correct! $\endgroup$ – Aqua Jan 27 '19 at 14:40
  • 1
    $\begingroup$ Is that better? $\endgroup$ – Aqua Jan 27 '19 at 14:52
  • 1
    $\begingroup$ What about now? $\endgroup$ – Aqua Jan 27 '19 at 15:51
  • 1
    $\begingroup$ Just put first and last expression on one side, so you get 0 on other side $\endgroup$ – Aqua Jan 27 '19 at 16:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.